Reforming legal framework for administration of estates in West Malaysia: an overview - Halim, Akmal Hidayah (Sweet & Maxwell Asia, 2013)
The area of administration of estates in West Malaysia is currently governed by various statutes and procedures which confer different jurisdiction to different categories of administrative bodies, depending on the types of estates left by the deceased. Undeniably, the presence of various laws and administrative bodies has led to non-uniformity in the law and procedure for the administration of estates. Hence, this paper aims to analyse whether reforming the law is necessary in order to achieve uniformity and to further expedite the administration process. An analysis is made on the law and procedure as provided by the statutes governing the administration of estates in West Malaysia. These include analysing existing legal and procedural weaknesses and examining the proposed legal reform. This paper also predicates that a single, competent body dealing specifically with the matter should be established to achieve uniformity in the law and procedure for the administration of estates in West Malaysia.